Magnitude and outcomes of road traffic accidents at Hospitals in Wolaita Zone, SNNPR, Ethiopia - Hailemichael, Feleke (BMC Res Notes, 2015)
BACKGROUND: A Road traffic accident is an incident on a way or street open to public traffic, resulting in one or more persons being killed or injured, and involving at least one moving vehicle. METHODS: The aim of this study is to assess magnitude and outcome of road traffic accidents among trauma victims at hospitals in Wolaita zone. A cross sectional hospital based study design using retrospective chart review was conducted from March 5th to March 25th, 2014. Simple random sampling technique was applied to identify sample population. The data was entered in to Epi info version 3.5.1 and transferred to SPSS version 16 for further analysis. RESULTS: A total of 384 trauma victims were incorporated in the study of which 240 (62.5%) were due to road traffic accidents. The majority of patients were male 298 (77.6%) and most commonly aged between 20–29 (35.42%). The principal outcome of injury was more commonly lower extremity (182 patients, 47.4%), compared to upper extremity (126 patients, 32.8%). CONCLUSION: Of all trauma patient presenting to hospitals (62.5%) are the result of road traffic accident. Hence, the provision of tailored messages to all members of the community regarding knowledge and practices of road safety measures like appropriate use of pavements by pedestrians and avoiding risky driving behaviors. Besides this make use of compulsory motorcycle helmets would appear to be a very important intervention